"Hell no, they'll think you're mad as a hatter": Illness discourses and their implications for patients in mental health practice. (March 2016) - Ringer, Agnes; Holen, Mari
This article examines how discourses on mental illness are negotiated in mental health practice and their implications for the subjective experiences of psychiatric patients. Based on a Foucauldian analysis of ethnographic data from two mental health institutions in Denmark—an outpatient clinic and an inpatient ward—this article identifies three discourses in the institutions: the instability discourse, the discourse of "really ill, " and the lack of insight discourse. This article indicates that patients were required to develop a finely tuned and precise sense of the discourses and ways to appear in front of professionals if they wished to have a say in their treatment. We suggest that the extent to which an individual patient was positioned as ill seemed to rely more on his or her ability to navigate the discourses and the psychiatric setting than on any objective diagnostic criteria. Thus, we argue that illness discourses in mental health practice are not just materialized as static biomedical understandings, but are complex and diverse—and have implications for patients' possibilities to understand themselves and become understandable to professionals.